One-year endurance training: Effects on lung function and airway inflammation - Denguezli, M.; Chiekh, I. B.; Saad, H. B.; Zaouali-Ajina, M.; Tabka, Z.; Zbidi, A. (Journal of Sports Sciences, 2008)
The aim of this study was to determine whether endurance training in athletes induces airway inflammation and pulmonary function disorders. Respiratory pattern and function were analysed in ten healthy endurance runners at rest, during sub-maximal exercise, and during the recovery. Inflammatory cells and metabolites (histamine, interleukin-8, and leukotriene E4) were measured in sputum at rest and after exercise. The experiments were conducted on three different occasions (basic endurance training, pre-competitive and competitive periods). In spite of the absence of post-exercise spirometric changes and respiratory symptoms, airway cells counts and inflammatory markers changed significantly. At the beginning of the experiment, athletes' induced sputum showed an abundance of macrophages compared with neutrophils. We found a high percentage of neutrophils during the pre-competitive and competitive periods of the sport season (41% and 37%), a significant increase in macrophage counts during the pre-competitive period (51%), and a significant rise in total cells, interleukin-8, leukotriene E4, and histamine during the competitive period. In conclusion, one year's training increased markers of inflammation in the airways of endurance runners without symptoms or changes in pulmonary function, suggesting that airway inflammation is of insufficient magnitude to markedly impact lung function in healthy athletes.